(untitled) - Tran, Thi Thap Hieu (Can Tho, 2018)
This book introduce about effect of salinity and elevated temperature on maintenance requirements and efficiency of feed utilization. The effect of salinity at elevated temperature on protein and lipid requirements in red tilapia.
Keywords: Nuôi cá,Fish culture; Nghiên cứu,Research